Ekonomi Islam : Angkatan Kerja, Tingkat Partisipasi Angkatan Kerja, Status Perokok Aktif Terhadap Pertumbuhan Ekonomi - Vega, Aeylen Amanda; Putri, Rosydalina; Setyanto, Alief Rakhman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to analyze the effect of the labor force, labor force participation rate, and active smoking status on economic growth in Indonesia during the period 2019–2024 from an Islamic economics perspective. The data used are panel data sourced from the Central Statistics Agency (BPS) and analyzed using a quantitative approach with the Common Effect Model (CEM) method through EViews software. The results of the t-test indicate that, partially, the labor force and labor force participation rate do not have a significant effect on economic growth, with probability values of 0.7178 and 0.8951 (> 0.05), respectively. Meanwhile, active smoking status has a significant effect on economic growth, with a coefficient value of 0.039842 and a probability of 0.0080 (< 0.05). Simultaneously, the labor force, labor force participation rate, and active smoking status do not have a significant effect on economic growth, with an F-statistic value of 0.278473 and a probability of 0.840896 (> 0.05). From an Islamic economics perspective, economic growth is not only measured by increased output but must also consider the quality of human resources and public health as part of the maqāṣid al-sharī‘ah, particularly the preservation of life (ḥifẓ al-nafs) and wealth (ḥifẓ al-māl). Therefore, development policies should focus on improving labor quality and controlling smoking behavior to achieve sustainable and equitable economic growth.